On generalized Jørgensen inequality in SL(2,C) - Gongopadhyay, Krishnendu (Sobolev Institute of Mathematics, 2019)
Wang, Jiang and Cao have obtained a generalized version ofthe J rgensen inequality in Proc. Indian Acad. Sci. Math. Sci., 123(2):245–251, 2013, for two generator subgroups ofSL(2;C)where one of thegenerators is loxodromic. We prove that their inequality is strict
Only IISERM authors are available in the record.
Keywords: J rgensen inequality; Discreteness; Proc